Analisis dan Implementasi Dashboard Monitoring Program Link and Match Perguruan Tinggi Berbasis Google Sheet - Farah Shofiyah; Yekti Wirani (LPPM STT Terpadu Nurul Fikri, 2021)
The Link and Match lecture system is a lecture program created to combine the higher education curriculum with the needs of the world of work. Since implementing the Link and Match learning system at STT Terpadu Nurul Fikri, which has been running in 2019, there have been administrative problems such as difficulties in seeing Presence, final grades, and student performance in link and match. This research aims to build a Link and Match Information System Dashboard Using Google Sheet that facilitates managing and administering the Link and Match Program. The research method used in this study uses the Mix Method research method, which combines qualitative and quantitative research and uses Scrum for the dashboard development method. The test results from the Implementation of the Link and Match Information System Dashboard are 100% for Students and 98.9% for Lecturers, which means that the existence of this Dashboard makes it easier to monitor the administration and management of the Link and Match dashboard. The Link and Match Information System provide a feature to view Student Final Scores, Student Attendance Percentage, Recap of Group Presence for each sprint, Student Presence Level with a percentage of >75% and <75%, Percentage of group point reduction, Individual point reduction percentage, Highest and lowest score of 3 students, Comparison of group scores in each sprint and Student Activity Logbook.